A phenomenological study into Zimbabwean-Australian clergy’s understandings of the causes and their responses to mental health problems among Zimbabwean Australians - Mafuriranwa, Richard (Curtin University, 2024)
This thesis investigates how Zimbabwean-Australian clergy address mental health needs within their community. Using Interpretative Phenomenological Analysis (IPA), interviews with 16 clergy members revealed that mental health issues are attributed to both spiritual and psychological factors. Clergy often act as first responders but lack formal training, highlighting the need for collaboration with mental health professionals and tailored training programs. Addressing both spiritual and psychological aspects is crucial for supporting the Zimbabwean-Australian community effectively.